Does intellectual capital explain the financial performance of Malaysia MFIs? / Maryam Jameelah Hashim, Syed Musa Alhabshi and Nor Irvoni Mohd Ishar - Hashim, Maryam Jameelah; Alhabshi, Syed Musa; Mohd Ishar, Nor Irvoni (Penerbit UiTM (UiTM Press), 2018)
The performance of microfinance institutions (MFIs) is crucial for ensuring the efficient utilisation of funds deposited into the microfinance programme by donors, as well as for assisting regulators in monitoring the institutions. Assessing the performance of MFIs involves examining its development towards accomplishing its goals. Therefore, MFIs need to ascertain the challenges to maintain their sustainability and sustain their operations. Additionally, MFIs should focus on aspects such as intellectual capital (IC) to ensure future sustainability. The aim of this research is to examine how IC dimensions, specifically, customers, structure, human, and social capital, influence MFIs performance. A cross-sectional survey design was used to gather data from 145 managers (48% response rate) from MFIs in Malaysia. In order to determine the sample size of the study, a purposive sampling method was employed. The research model was analysed by using Partial least square-structural equation (PLS-SEM). Subsequently, the research model was validated using Smart PLS 3.2.5 and the proposed study hypothesis. The findings confirm that structural capital and customer capital positively influence the performance of MFIs, except for social and human capital. The research model explains 67.6% of the substantial amount of variance in MFIs performance. This research theoretically contributes to the extension of resource-based view (RBV) and social capital theory in predicting the sustainability of MFIs. All the factors of IC were confirmed to improve the performance of MFIs. This study proposed several remarkable recommendations for microfinance institutions which suggested that MFIs’ managers should resolve their organisational issues promptly. Furthermore, they should portray sensible consideration for their institutions by taking care of IC and encouraging the practice of recognising intangible assets, especially their employees’ expertise and capabilities.